Revitalisasi Paradigma Pendidikan Islam Inklusif Sebagai Penguatan Moderasi Beragama di Pesantren - Ngarifin Shidiq; Muhamad Yusuf Amin Nugroho (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
This paper seeks to refresh the importance of inclusive Islamic education as a strategy to strengthen religious moderation in Islamic boarding schools. Through sufficient understanding of inclusive Islamic education, it is hoped that the campaign for religious moderation through Islamic boarding schools will gain a strong philosophical footing. This research is a literature study, using reference sources and documents specifically related to inclusive Islamic education in Islamic boarding schools. Islamic boarding schools have a strategic position and role in maintaining a moderate Islamic ideology and have long been known as inclusive educational institutions. The inclusive attitude of pesantren is represented through the understanding that Islam is a religion that emphasizes openness, humanism, equality and tolerance. Inclusive Islamic education, which has been the hallmark of Islamic boarding schools since its emergence, must be used as a basis for reinforcing religious moderation in Islamic boarding schools